Dermoid cyst in the tonsil - a case study - Anwar, Mostafa Mahfuzul; Rahman, Md Zillur (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v19i2.3874 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):57-58